The Effectiveness of Value Clarification Technique Learning Model on Students' Learning Outcomes - Restu Yanuar Ula; Sarkadi Sarkadi; Aip Badrujaman (Jurnal Pendidikan dan Pengajaran, 2021)
Improving the quality of education is based on the formation of the quality of learning through teacher competence in managing the classroom. However, the problem is that the learning outcomes of history are still relatively low because the competence of teachers in applying the method is still monotonous. On the other hand, the VCT learning model can provide creative-critical power, foster positive attitudes, interests, and values in students in learning history. Therefore, this study aims to determine the effect of the Value Clarification Technique learning model on student learning outcomes of history. The research method used quantitative methods with a quasi-experimental design. The research design used was the Non-Equivalent Pretest-Posttest Design. The population in this study was all students of grade XI. At the same time, the sampling technique is purposive sampling which is divided into two classes into the experimental group and the control group. The results of this study indicate that the VCT learning model affects student learning outcomes in history learning.